Plotino e Adorno: alcuni parametri di visioni estetiche - Sanfilippo, Crispino (Peitho. Examina Antiqua, 2025)
This article proposes a comparison between the aesthetic vision of Plotinus and that of Theodor W. Adorno, two distant thinkers – not only in time – but not for this reason not comparable to each other in the possibility of a dialogue on the way in which respectively they conceive the relationship with beauty. An attempt is made to address the topic through some parameters that structure the distinction between looking and theoretical vision, and therefore that between the object of sensation and its true content, giving prominence to the metaphysical slant of aesthetic theory. The speculative proposals of Proclus and Hume are then used methodologically to highlight links and contrasts with Neoplatonism and contemporary philosophy.